Chronopharmacology of verapamil in Stage I-II arterial hypertension - V. G. Belolipetskaya; D. F. Guranda; E. Yu. Fedorova; V. M. Gorbunov; N. A. Belolipetsky; A. V. Zhezlova; O. Yu. Isaykina; E. A. Zhabina; I. E. Koltunov (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To compare the pharmacokinetics and pharmacodynamics of verapamil retard, regularly taken by patients  with Stage I-II arterial hypertension (AH). Material and methods. The effects of the administration time (morning vs. evening) on verapamil retard pharmacokinetics were investigated. This open, randomised, cross-over study included 14 patients with Stage I-II AH,  who were regularly administered verapamil retard for 3 weeks. Before the active therapy started, all antihypertensive medications were withdrawn, with an exception of short-acting agents (“wash-out” period). Two weeks later,  the patients were administered verapamil retard, according to the randomisation scheme, and were recommended  to take one tablet in the morning or evening, at the same time every day. The first administration was at the clinic,  under medical supervision. Three weeks later, the participants were hospitalised for pharmacokinetics assessment. Seven days after the end of the first treatment course, a second course started, with an inverted time of verapamil retard administration. Blood concentration of non-modified verapamil was measured by high-performance liquid chromatography with fluorescent detection.Results. Significant differences in pharmacokinetics were observed for morning vs. evening verapamil administration. The respective maximal verapamil concentrations were 239,7±152,3 vs. 148,6±107,4 ng/ml (p<0,01), and respective half-life times were 12,50±3,48 vs. 22,57±15,24 hours (p<0,05). For other parameters, the difference was non-significant.Conclusion. In Stage I-II AH patients, the morning administration of Isoptin SR resulted in accelerated increase of its plasma concentration. At the same time, the evening administration was associated with increased half-life time and higher “concentration-effect” correlation, which makes the latter variant more rational.